Noggin Attenuates Cerulein-Induced Acute Pancreatitis and the Impaired Autophagy - Cao, Yanna (2013)
OBJECTIVES: To investigate the role of bone morphogenetic protein (BMP) signaling in acute pancreatitis (AP) by administration of noggin, an endogenous BMP antagonist, in a cerulein-induced AP model. METHODS: AP was induced by 9 hourly intraperitoneal injections of cerulein (50 µg/kg). Control mice received PBS injections. In a separate group, noggin (0.5 mg/kg) was given intraperitoneally at 1 hour before, and 2, 4, and 6 hours after AP induction. The mice were euthanized at one hour after completion of AP induction. The blood samples and the pancreas were harvested for analysis. Isolated pancreatic acini from normal mice and AR42J cells were treated with BMP2 and cerulein. AR42J cells were also treated with noggin. Phosphorylation of Smad1/5/8 was measured. RESULTS: BMP signaling was upregulated in AP mouse pancreas. BMP2 and cerulein induced phosphorylation of Smad1/5/8 in the acinar cells in vitro, which was blocked by noggin. Noggin administration in vivo attenuated AP induction, decreased vacuole formation in acinar cells, blocked LC3-II levels and partially restored Beclin-1 and Lamp-2 levels. CONCLUSIONS: BMP signaling appears to promote AP induction and autophagy, as suggested by our study showing that noggin ameliorates AP and partially restores autophagic homeostasis.